Pioneering the Green Sukuk : Three Years On - World Bank (World Bank, Washington, DC, 2020)
This note is a stocktaking of the first three years of the green sukuk. Given the small sample size and limited data, the analysis is limited in scope. It covers the basics of what makes a green sukuk, a brief history of the developmental work leading to the first green sukuk, followed by an assessment of the green sukuk market to date, before concluding with some key challenges and opportunities and what this could mean for policy makers and regulators.